A 10-year audit of gynaecological surgeries performed in the paediatric age group at the Jos University Teaching Hospital - Ekwempu C; Ocheke A; Uba F (Wolters Kluwer Medknow Publications, 2010)
Background: Surgeries performed for gynaecological conditions in children and adolescents are not common in our environment. Adequate facilities and the skill to perform the required procedures may also be lacking. We were interested in reviewing the practice of paediatric gynaecological surgery in our facility. Patients and Methods: A retrospective study of case files and theatre records of children below the age of 16 years who had surgeries at the Jos University Teaching Hospital over a 10 year period was undertaken. Results: A total of 89 surgeries were performed in this age group during the period under review. Twenty-eight (33.4%) of the patients were below the age of 11. The most common surgical procedure was for the management of septic abortion (21.3%). Correction of congenital malformations of the genital tract accounted for 21.4% (19) of the surgeries performed. Fourteen (15.7%) laparotomies were performed for ovarian cysts. Conclusion: Though the number of surgeries performed on children for gynaecologic reasons may appear small, the skills required to manage them should be enhanced and the requisite facilities provided.